FLORISTIC COMPOSITION AND STRUCTURE OF VEGETATION IN GUNUNG SALAK GEOTHERMAL POWER PLANT, WEST JAVA, INDONESIA - Afri Irawan; Peniwidiyanti Peniwidiyanti; Ainurrofiah Ainurrofiah; Heri Destrianto; Mulyadi Kusumah; Vicky Apriandana (BRIN Publishing (Penerbit BRIN), 2023)
This research had been conducted in the forest area around the Gunung Sa-lak Geothermal Power Plant of PT. PLN Indonesia Power. Plant diversity data in the geothermal power plant area had yet to be fully available. This study aimed to analyze the composition and structure of vegetation in the conservation forest area around the Gunung Salak Geothermal Power Plant unit. This study used a quadrat plot with a purposive sampling method. We sampled 873 individuals from 56 families of 110 species, consisting of native and introduced species. Some introduced flora species that have the potential to become invasive include Calliandra houstoniana, Asystasia gangetica, Bellucia pentamera, Miconia crenata, Maesopsis eminii, and Solanum torvum. The families with the highest number of species at each growth level were Fagaceae (tree), Fagaceae (pole), Arecaceae and Moraceae (sapling), also Acanthaceae, Arecaceae, Melastomataceae, and Poaceae in the understory. Several species of plant at the site are listed as Endangered (EN) based on the IUCN Red List, including Alpinia scabra, Castanopsis argentea, and Dipterocarpus hasseltii. These endangered plants are expected to become priority for conservation strategies and action plans. The Important Value Index (IVI) analysis shows different values at each growth stage. The highest IVI at the seedling and herb was Selaginella plana (29.74), the sapling was Macaranga triloba (20.59), the pole was Ficus fistulosa (43.27), and the tree was Schima wallichii (54.90). The value of the Shannon-Wiener (H') diversity index was 3.784, which indicates that the level of diversity is high.